2017
DOI: 10.1038/s41598-017-01669-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergic bactericidal effects of reduced graphene oxide and silver nanoparticles against Gram-positive and Gram-negative bacteria

Abstract: Reduced graphene oxide (rGO) is a promising antibacterial material, the efficacy of which can be further enhanced by the addition of silver nanoparticles (nAg). In this study, the mechanisms of antibacterial activity of rGO–nAg nanocomposite against several important human pathogenic multi-drug resistant bacteria, namely Gram-positive coccal Staphylococcus aureus and Gram-negative rod-shaped Escherichia coli and Proteus mirabilis are investigated. At the same concentration (100 µg/ml), rGO–nAg nanocomposite wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 83 publications
4
94
0
Order By: Relevance
“…Recently, we discovered that ultra-small 1-2 nm silver (and gold) nanoparticles synthesised in an aqueous medium have a very high potency against a range of clinically relevant pathogens, but also reduce expression of pro-inflammatory cytokines from immune cells and help wounds to close [88][89][90]. We also combined silver nanoparticles and graphene oxide nanostructures and demonstrated a synergic bactericidal effect against Gram-positive and Gram-negative bacteria [81]. Figure 2), while the AgNPs release silver ions to eliminate bacteria in the vicinity of the substrate.…”
Section: Silver Containing Coatings and Materialsmentioning
confidence: 99%
“…Recently, we discovered that ultra-small 1-2 nm silver (and gold) nanoparticles synthesised in an aqueous medium have a very high potency against a range of clinically relevant pathogens, but also reduce expression of pro-inflammatory cytokines from immune cells and help wounds to close [88][89][90]. We also combined silver nanoparticles and graphene oxide nanostructures and demonstrated a synergic bactericidal effect against Gram-positive and Gram-negative bacteria [81]. Figure 2), while the AgNPs release silver ions to eliminate bacteria in the vicinity of the substrate.…”
Section: Silver Containing Coatings and Materialsmentioning
confidence: 99%
“…Both the Ag‐ and Cu‐based monometallic graphene composites were reported to suppress bacterial growth, in particular, Ag‐based graphene composite showed higher antibacterial activity as compared to the Cu‐based graphene composite . Recently, several important multi‐drug resistant bacteria have been successfully treated by using the antibacterial activity of reduced graphene‐silver nanocomposite . The development of recyclable and synergistic graphene oxide nanocomposite was reported by using both silver nanoparticles and iron oxide nanoparticles as a novel multifunctional antibacterial material …”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
“…126 Recently, several important multi-drug resistant bacteria have been successfully treated by using the antibacterial activity of reduced graphene-silver nanocomposite. 127 The development of recyclable and synergistic graphene oxide nanocomposite was reported by using both silver nanoparticles and iron oxide nanoparticles as a novel multifunctional antibacterial material. 128 Numerous studies have confirmed that metal nanoparticles are effective against plant pathogens, pests and insects and, therefore, the topic is deserving of extended discussion.…”
Section: Nanotechnology-based Opportunities In Crop Protectionmentioning
confidence: 99%
“…Unlike B. subtilis , the rate of colonization by E. coli was not affected by plasma treatment. On surfaces with sharp nanoscale features, contact killing of cells through mechanical deformation of the membrane can take place . Generally, Gram‐negative bacteria, such as E. coli , have cell walls that are more susceptible to carbon‐nanotube‐induced morphological deformation than those of the Gram‐positive strains, e.g., B. subtilis .…”
Section: Overview Of Application Of Self‐assembled Hierarchical Metammentioning
confidence: 99%